Kampung Susu Lawu on the slopes of Mount Lawu as a tourist destination - Agustinus Doedyk Setiyawan; Priyanto; Aminudin Azis (International Journal of Applied Sciences in Tourism and Events, 2023)
This study aims to analyze the potential attractiveness of tourist destinations and the obstacles faced in developing the tourism potential of Kampung Susu Lawu on the slopes of Mount Lawu, Magetan Regency, East Java, Indonesia. It uses a qualitative descriptive research method. Data collection techniques were carried out by triangulation, with inductive data analysis using more than one data acquisition method. The results of the study show that the tourist destination of Kampung Susu Lawu (KSL or Lawu Milk Village), actually has a potential attraction that can be enjoyed by tourists which includes nature, culture, and man-made. Land management permits are expected to increase the welfare of tourism workers, open up job opportunities, provide a source of income for families, increase the variety of jobs, and increase knowledge in tourism business management.